Global Perspectives and Key Debates in Sex and Relationships Education: Addressing Issues of Gender, Sexuality, Plurality and Power - Sundaram, Vanita; Sauntson, Helen; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
There is a great variety of sex and relationship education in the global North and South and this book draws together the global perspectives and debates on this key topic. Issues including gender-based violence, pornography, sexual consent, sexual diversity and religious plurality are all discussed with reference to cutting-edge research.
Keywords: Sociology; Gender and Education